Effect of glucono-δ-lactone on the structural characteristics of red seabream (Pagrosomus major) surimi. Issue 109 (9th November 2016) - Fan, Daming; Huang, Luelue; Yang, Feng; Zheng, Yan; Cao, Hongwei; Huang, Jianlian; Liu, Xiaoming; Zhao, Jianxin; Zhang, Hao
Abstract : The influences of glucono-δ-lactone (GDL) on the structural characteristics of red seabream ( Pagrosomus major ) surimi gel were studied in terms of protein components, secondary structure and aggregation of protein under pasteurisation conditions. Abstract : The influences of glucono-δ-lactone (GDL) on the structural characteristics of red seabream ( Pagrosomus major ) surimi gel were studied in terms of protein components, secondary structure and aggregation of protein under pasteurisation conditions. The results showed that most of the salt-soluble protein form a gel, and a small amount of water-soluble protein plays a role in the addition of GDL under low-temperature heating conditions during surimi gel formation. The active sulfhydryl content of actomyosin increased but the total sulfhydryl content decreased as the content of GDL increased. The percentage of β-folds increase and that of α-helices decreased as the content of the GDL increased. SDS-PAGE results suggest that adding GDL can induce more MHC cross-linking and that the degree of cross-linking is higher than that in the high-temperature treatment samples.